Eastern hemisphere (New York : Macmillan/McGraw Hill School Pub. Co., 1991)
Geographical approach to nations of Europe, Africa, Asia, and Australia, which acquaints students with social structures of countries covered.
Keywords: East and West; Eastern Hemisphere -- Description and travel; Eastern Hemisphere